THE DEVELOPMENT OF PAI LEARNING METHODS (ASPECTS OF TYPES AND ITS SUPPORTS) - Ernaka Heri Putra Suharyanto; Laily Nur Arifa; Muh. Barid Nizarudin Wajdi (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2021)
AbstractThere are not many methods of learning Islamic education (PAI) that have become the choice of educators (teachers and lecturers), but from the choice of learning methods that are often chosen, there are still weaknesses in their application, so it is important to discuss the development of the methods. PAI learning in the aspect of types and supports. The method used in writing this article is in the form of a literature review which is a study with a tendency to carry out text or discourse analysis activities and is an investigation of an event related to the actions or writings being studied in order to obtain various relatively precise facts related to the development of the PAI learning method. in terms of types and supports.